Pandangan Medis terhadap Praktik Puasa antara Spiritualitas dengan Ilmu Kesehatan - Jaziroh, Amelia Zulfa Zilmi; Wicaksono, Arya Candra Wahyu; Aufa, Ni’ma Khusnatul; Amiruddin, Muhammad (Maliki Interdisciplinary Journal, 2025)
For centuries, fasting has been known as part of spiritual and religious traditions. However, the medical world is now beginning to recognize the hidden benefits of this practice. This article explores the potential of fasting therapy from a medical perspective by reviewing various studies and the latest clinical evidence. Various forms of fasting, such as intermittent and prolonged fasting, have been shown to have positive effects on the body, from balancing metabolism and improving cell function to helping prevent chronic diseases such as type 2 diabetes, heart disease, and neurodegenerative diseases. Furthermore, fasting can trigger important processes in the body such as autophagy, increase insulin sensitivity, and reduce inflammation. Beyond the physical aspects, this article also explores the psychological and ethical dimensions of fasting as therapy. With a more holistic approach, fasting therapy can be a safe, effective, and natural option to support overall health. This reflection encourages medical professionals and the public to consider fasting not only as a religious practice but also as a holistic preventive and healing measure.